Images in the New Testament: An Interdisciplinary Iconology for Biblical Interpretation - St Pierre, Ashley (My University, 2026)
“Images in the New Testament: An Interdisciplinary Iconology for Biblical Interpretation” Ashley St Pierre McMaster Divinity College Hamilton, Ontario Master of Divinity, 2026 This thesis explores different ways to think about images and how they are meaningful in order to work towards a theory of imagery for biblical interpretation, engaging with biblical iconology to clearly define imagery and its use in the NT in a way that better accounts for cases of ambiguous image appropriation and association. Several distinct fields of study relating to experiencing and understanding representations and their associations each contribute something valuable to the interpretation of NT imagery. A hermeneutical theory of imagery in the NT should attempt to integrate these interdisciplinary insights thus offering a more sophisticated and nuanced understanding of imagery and its use. The thesis proposes that such a theory would benefit from synthesizing theoretical frameworks drawn from notions of visuality, textuality, semiotics, metaphor theories, and cognitive science.